Identification and splicing analysis of the first deep intronic FIG4 variant causing Yunis–Varon syndrome - Tang, Hui; Chen, Qingqing; Xiang, Jingjing; Zhang, Qin (Frontiers in Genetics, 2025)
Yunis–Varón syndrome (YVS) is a severe autosomal recessive syndrome caused by mutations in the FIG4 gene. It is characterized by skeletal defects, including cleidocranial dysplasia and digital anomalies, and a poor prognosis due to neurological and cardiovascular involvement. In this study, we observed a Chinese family with three patients presenting thumb and hallux dysplasia. Whole-genome sequencing (WGS) identified a compound heterozygous variant in the proband: c.2097-809A>G and c.1141C>T (p.R381*). The c.2097-809A>G variant generated an aberrant splicing transcript containing a pseudoexon from intron 18, as demonstrated by further RT-PCR and splicing analysis. This is the first deep intronic variant reported in the FIG4 gene. In addition, we provided prenatal diagnoses for the family. This study expands the genetic variant spectrum, provides additional molecular and clinical information, and broadens our understanding of the molecular mechanisms involved in the disease course.